2019
DOI: 10.1111/jnc.14793
|View full text |Cite
|
Sign up to set email alerts
|

Plasma kallikrein‐kinin system contributes to peripheral inflammation in temporal lobe epilepsy

Abstract: Temporal lobe epilepsy (TLE) is a chronic disease, characterized by severe and refractory seizures, triggered in the hippocampus and/or amygdala, disrupting the blood–brain barrier. This disruption can sustain, or aggravate, the epileptic condition. The aim of this study was to evaluate the activation of the kallikrein‐kinin system in patients with TLE, as it relates to the maintenance of blood–brain barrier. Human hippocampal sclerotic tissues removed after surgery for seizure control, plasma, and serum were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The increased expression of CysC was observed in glial cells in the molecular layer of the dentate gyrus and associated with granule cell dispersion in both rat model and human patients with TLE ( 4 ). High levels of CatB were reported in serum of human patients with surgically resected temporal lobes ( 59 ) and in glial cells of progressive myoclonic epilepsies ( 57 ), suggesting that CatB can be a potential therapeutic target for certain epilepsies ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of CysC was observed in glial cells in the molecular layer of the dentate gyrus and associated with granule cell dispersion in both rat model and human patients with TLE ( 4 ). High levels of CatB were reported in serum of human patients with surgically resected temporal lobes ( 59 ) and in glial cells of progressive myoclonic epilepsies ( 57 ), suggesting that CatB can be a potential therapeutic target for certain epilepsies ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that systemic inflammatory responses reflected by NLR remained increased during 5–14 days of follow-up after acute seizures compared with healthy controls. Some studies have also found that NLR level is higher in patients with chronic temporal lobe epilepsy than in healthy controls ( 39 ). Accordingly, it is suggested that the long-lasting systemic inflammatory response induced by acute seizures may be involved in the process of epileptogenesis either in the acute stages or in the chronic stages.…”
Section: Discussionmentioning
confidence: 99%
“…The role and contribution of PKall to aging and neurodegenerative disorders are still being unraveled ( Albert-Weissenberger et al, 2014 ; Nokkari et al, 2018 ; Strickland 2018 ). Higher levels of circulating PKall activity were associated with augmented KNG cleavage resulting in the greater generation of BK levels which could influence vascular dysregulation in states of neurodegenerative diseases ( Zamolodchikov et al, 2015 ; Simoes et al, 2019 ; Park et al, 2021 ). Mice lacking the PKall gene (klkb1), displayed reduced brain infarctions and fewer neurological shortfalls compared to wild-type mice when subjected to brief central cerebral artery obstruction ( Gob et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%